CONSUMER PROTECTION AGAINST WITHDRAWAL OF MOTOR VEHICLES BASED ON FIDUCIAN COLLATERAL - Jannus Manurung; Yuniar Rahmatiar; Muhamad Abas (Universitas Muhammadiyah Tangerang, 2023)
In the current era, all people can own a motorized vehicle in an easy and fast way. This is triggered by the way to buy a motorized car with credit. In terms of withdrawing vehicles, finance companies use the role of a third party (a debt collector) to carry out their actions in collecting creditors and also carrying out forced withdrawals of collateral objects, where the financing company feels that the actions taken are safe. A debt collector is a third party who assists a finance company in resolving a credit problem that the finance company cannot determine. The problem is how the collector department's implementation of the motorized vehicle withdrawal process is linked to law number 42 of 1999 concerning fiduciary guarantees and how consumer protection for motorized vehicle withdrawals by the collector department is linked to law number 42 of 1999 concerning fiduciary contracts. The research method is qualitative, with the approach used in this research being normative juridical. The results of his study show that Consumer Protection Against Motor Vehicle Withdrawal has not gone well because when a consumer's motorized vehicle has been withdrawn, there is no further information on the vehicle's whereabouts, whether it is being sold or auctioned. So that when the car is going to be auctioned or sold, the consumer needs to know that the result is more than or sufficient to pay off the consumer's debt. Many unscrupulous debt collectors do not have a clear professional status and sometimes threaten consumers, which causes harm to consumers and the most crucial factor they register. A fiduciary Guarantee is the registration of a motorized vehicle as a fiduciary guarantee to have legal certainty for both the party providing the financing and the party receiving the funding. No legal counseling is carried out to the Financing Company related to fiduciary guarantees, especially in registering fiduciary collateral goods, where registration of fiduciary warranties is basically to obtain legal certainty over the object's position fiduciary as well as confidence for the parties agreeing within it.Keywords: Legal Protection, Consumers, Debt Collector